2015
DOI: 10.1093/humrep/dev082
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diagnostic criteria on the reproducibility of the hysteroscopic diagnosis of the septate uterus: a randomized controlled trial

Abstract: No study funding was received and no competing interests are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
16
1
Order By: Relevance
“…2013, it was shown that in infertile patients the international agreement on the diagnosis of the septate uterus and arcuate uterus by office hysteroscopy appeared to be rather disappointing [27]. The same findings were found in a subsequent study by the same authors even when some diagnostic criteria were used at time of office hysteroscopy [28]. Therefore, the consensus on the accuracy of office hysteroscopy during assessment of the uterine shape seemed to be poor, especially for the less profound variations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…2013, it was shown that in infertile patients the international agreement on the diagnosis of the septate uterus and arcuate uterus by office hysteroscopy appeared to be rather disappointing [27]. The same findings were found in a subsequent study by the same authors even when some diagnostic criteria were used at time of office hysteroscopy [28]. Therefore, the consensus on the accuracy of office hysteroscopy during assessment of the uterine shape seemed to be poor, especially for the less profound variations.…”
Section: Discussionmentioning
confidence: 92%
“…Many investigators found office hysteroscopy to be a valuable method to screen for congenital anomalies of the uterine cavity [7,8,17]. However, we believe that such subtle anomalies can be missed if uterine distension is not adequate, as commonly happens during office hysteroscopy to avoid patients' discomfort [19,27,28]. A recent video abstract suggested that even a diagnostic hysteroscopy, performed under modified general anesthesia, can miss the diagnosis of such anomalies if uterine distension is suboptimal [3].…”
Section: Discussionmentioning
confidence: 98%
“…An international multirater agreement study based on assessment of hysteroscopic videos, in which criteria for septate, arcuate and normal uterus were not provided for raters, showed poor agreement, especially between the most experienced hysteroscopists. A consecutive study, with raters assigned randomly to two groups, one with and one wthout definition of specific criteria, showed moderate agreement in both groups. Although weaknesses of these estimations were identified, these two studies may indicate that hysteroscopy with subjective judgment should not be used as the reference standard for distinguishing between a normal/arcuate and septate uterus in borderline cases.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies suggested that TV 3D US is accurate in diagnosis of PSU based on comparison with the findings on office hysteroscopy [10,26,27]. However, other investigators suggested that the reproducibility of diagnosing intrauterine abnormalities through office hysteroscopy appeared to be disappointing [28][29][30]. In addition, a recent video abstract suggested that even a diagnostic hysteroscopy, performed under modified general anesthesia, can miss the diagnosis of such anomalies if uterine distension is suboptimal [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent video abstract suggested that even a diagnostic hysteroscopy, performed under modified general anesthesia, can miss the diagnosis of such anomalies if uterine distension is suboptimal [31]. The latter commonly happens during office hysteroscopy to avoid patients' discomfort [29,30,32].…”
Section: Discussionmentioning
confidence: 99%